Deposition of boron-containing coatings by electron-beam evaporation of boron-containing targets. Issue 4 (March 2020) - Yushkov, Yu.G.; Oks, E.M.; Tyunkov, A.V.; Corbella, C.; Zolotukhin, D.B.
Abstract: Boron-containing films are promising materials for improving the hardness, wear-resistance and durability of mechanical parts used in industry. We describe a novel approach for deposition of such coatings – by using electron-beam evaporation of boron-containing target material (pure boron or boron nitride) in inert (helium) or chemically-active (oxygen, nitrogen, residual atmosphere) gases at medium vacuum. Boron-containing films deposited on titanium substrates were characterized using a nanohardness tester and a non-contact 3D profilometer. Elemental composition of the coatings was studied using raster electron microscope equipped with a device for EDX analysis. All boron-containing coatings provided significant improvement (by a factor of 4–16) in the microhardness of the substrate surface.